Prednisolone in the treatment of airflow obstruction in adults with cystic fibrosis. Issue 1 (January 1986) - Pantin, C F; Stead, R J; Hodson, M E; Batten, J C
Abstract : The effect of oral prednisolone on the lung function of 20 adult patients with cystic fibrosis who had severe stable airflow obstruction was assessed in a placebo controlled study, blind to the patients. Placebo tablets were followed by prednisolone given in a median dose of 0.48 mg/kg body weight/day (20 mg/day in 11 patients, 30 mg/day in nine patients), each for three weeks. No significant improvement was seen in lung function in the group after receiving prednisolone, and none of the individual patients had clinically useful improvements in lung function. Atopic subjects showed an improvement in evening recordings of peak expiratory flow rate (PEF) while taking prednisolone (p less than 0.05). Significant deterioration in forced expiratory volume in one second (FEV1) and forced vital capacity (FVC) was seen after withdrawal of prednisolone. Two patients developed pneumothoraces while taking prednisolone.